Impact of temperature on Bacillus cereus spore germination in ultra-high temperature chocolate milk - Ubong, Anyi; New, Chia Yeung; Chai, Lay Ching; Nur Fatihah, A.; Nur Hasria, K.; Nishibuchi, Mitsuaki; Son, Radu (Rynnye Lyan Resources, 2019)
Bacillus cereus spores are capable of surviving the harsh environment and more often, they cause great concern to the dairy industry. The current research was conducted to study the effect of temperature on germination and growth of B. cereus spores in UHT chocolate milk; the study was carried out at 8°C, 25°C and 35°C over a span of seven days. The results showed that no growth was observed at 8°C. At 25°C, a rapid increase in growth was observed as early as Day 1, from an initial count of ten spores to 4.01 log10 CFU/mL. Meanwhile, at 35°C, the growth on Day 1 was more rapid in which the count promptly increased to 8.07 log10 CFU/mL. Analysis of graph trend showed that the number of vegetative cells decreased while the number of spores increased with incubation time due to nutrients exhaustion. This study fills up the data gap towards understanding the possible issues that might arise in the actual scenario and at the same time, suggests a suitable approach to minimize infection risk caused by B. cereus spores. © 2019 The Authors.